2008
DOI: 10.1007/s00198-008-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

LCT 13910 C/T polymorphism, serum calcium, and bone mineral density in postmenopausal women

Abstract: LCT 13910 C/T polymorphism is associated with decreased serum calcium level and lower BMD in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(42 reference statements)
1
7
0
2
Order By: Relevance
“…The LCT‐13910 C/T genetic variant has been used as a proxy for milk intake in the present as well as in previous genetic analyses investigating the association with fractures , bone mineral density , bone turnover , Peripheral Quantitative Computed Tomography (PQCT) bone traits and serum calcium. Genetic analyses from the Danish cohorts alone suggested that a genetically lifelong intake of milk does not protect against hip fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCT‐13910 C/T genetic variant has been used as a proxy for milk intake in the present as well as in previous genetic analyses investigating the association with fractures , bone mineral density , bone turnover , Peripheral Quantitative Computed Tomography (PQCT) bone traits and serum calcium. Genetic analyses from the Danish cohorts alone suggested that a genetically lifelong intake of milk does not protect against hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…We also extracted sociodemographic and population characteristics from the studies. The studies excluded were a duplicate [24], data not shown [25] or not Northern European population study [26][27][28][29][30][31]. For statistical analyses, we used STATA 14.2.…”
Section: Meta-analysismentioning
confidence: 99%
“…Studies in postmenopausal women73 and elderly people74 with the LCT -13910CC genotype have identified lower bone mineral density and a higher incidence of bone fractures in comparison with individuals with other lactase genotypes. However, these results have not been confirmed by other studies75,76 or in younger subjects 69,77…”
Section: Managementmentioning
confidence: 99%
“…Thus, the lack of significant associations was probably due to the similar calcium intake reported in lactase nonpersistent and persistent participants, as in the present study (data not shown). 29 Because entering several nutrients into the same multiple regression analysis yielded invalid results because of the substantial collinearity between these variables, we only adjusted the regression model to the PRAL. There is increasing evidence that acid-base status has a significant effect on the skeleton, and diets with insufficient alkaline-forming foods or a net acid-producing diet may compromise bone health.…”
Section: Discussionmentioning
confidence: 99%